DAMPAK EKONOMI PENDIRIAN RITEL NASIONAL TERHADAP USAHA KECIL DI KECAMATAN TANJUNG REDEB KEBUPATEN BERAU: DAMPAK EKONOMI PENDIRIAN RITEL NASIONAL TERHADAP USAHA KECIL DI KECAMATAN TANJUNG REDEB KEBUPATEN BERAU - Fitriawati Fitriawati (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
The research aims to analyze how National Retail has developed in Tanjung Redeb District, Berau Regency and to analyze the positive and negative impacts of retail National support for small businesses in Tanjung Redeb District, Berau Regency. Based on the results of the data analysis carried out and the discussion that has been presented, it is concluded that the existence of Indomaret and Alfamidi as modern shops in Tanjung Redeb is increasingly shifting the existence of small shop owners who have traditional shops/kiosks selling the same merchandise. The number of consumers continues to decrease, which also has an impact on the income of small shop traders. Injustice is still felt by traders who own small shops. The existence of Indomaret and Alfamidi in Tanjung Redeb The existence of Indomaret and Alfamidi has both negative and positive impacts on society. The negative impact is felt by small shop traders who feel increasingly marginalized because of the existence of Indomaret and Alfamidi with cheap prices and much more complete goods.